Health Impacts of Road Traffic near School – a Narrative Review - Arif, Irfan; Jaweria, Aulliyah; Munir, Farwa (Pakistan Armed Forces Medical Journal, 2025)
Objective: to understand the comprehensive exploration of the stress that road traffic imposes on children, drawing on an extensive literature review that provides a thorough understanding of this issue. Methodology: A narrative review was meticulously planned, with a focus on selecting high-quality research studies published within the last 20 years. These studies, randomly chosen from reputable sources such as PubMed, Google Scholar, and Embase, provide a robust foundation for our findings. The keywords used for the database search were Road traffic, Health impacts of road traffic, traffic near schools, harms of traffic near schools, and road traffic stress among children. A total of 30 manuscripts, each contributing unique insights, were thoroughly reviewed. Results: The narrative review underscores the criticality of noise and air pollution, both stemming from road traffic, as significant challenges for the global population. The presence of tyre wear parts and particulate matter in the air, a direct result of road traffic, is linked to a range of health problems, including respiratory issues, immune health complications, and allergies. In children, these pollutants can trigger neurological problems such as ADHD and developmental issues. Conclusion: It is imperative to address road traffic stress, especially in the vicinity of schools, as it has profound and detrimental effects on children’s health. The health challenges faced by children are not to be taken lightly, as they are chronic and can lead to enduring neurological and developmental deficits. Taking steps to reduce traffic near schools is a crucial responsibility we all share.